Entrapped in one's blind spot: Perceptions of bias in others and preparation for deliberation. Issue 1 (March 2016) - Yan, Wenjie; Abril, Eulàlia P.; Kyoung, Kyurim; Jing, Gang
Taking different views into account is considered a virtue of democratic citizens. However, disagreement is often a barrier to deliberation. One reason is that individuals tend to impute biases to their adversaries and, on this basis, prepare for deliberation in less than optimal ways. Two experiments were conducted with results that supported this proposition. Specifically, encountering an incongruent opinion from another person led people to infer more bias in that person's reasoning and consequently, to be less willing to engage in subsequent discussion with that person, and to be less inclined of using deliberative strategies if they found themselves in the discussion. Furthermore, these deliberative choices were directly predicted by individuals' expectancy of their discussion partner's likely deliberativeness based on their perceptions of bias in the partner's reasoning. Together, the evidence suggests the operation of a cognitive bias blind spot that is likely to undermine individuals' preparation for deliberative engagement.